Seasonality and Biting Behavior of Mansonia (Diptera, Culicidae) in Rural Settlements Near Porto Velho, State of Rondonia, Brazil - Galardo, Allan Kardec R.; Hijjar, Andrea; Falcao, Liliane Leite O.; Carvalho, Dario P.; Ribeiro, Kaio Augusto N.; Silveira, Guilherme A.; Neto, Noel Fernandes S.; Saraiva, Jose F. [UNESP] (Oxford Univ Press Inc, 2022)
Mansonia (Diptera: Culicidae) are known to cause discomfort to the local populations of Amazon. Considering the fact that the effective control of these mosquitoes can only be obtained by understanding their ecology and behavior, entomological monitoring becomes essential. In view of this, mosquitoes of the genus Mansonia were collected by human landing catches (HLC) from 2015 to 2019, in four locations of Porto Velho, Rondonia, Brazil. The collections were performed inside and outside the homes, once in every four months, uninterrupted for 24 hr. Human bite indices/hour was used to analyze the hourly activity of the species for different seasons and environment (indoor and outdoor). Moreover, nonparametric Mann-Whitney tests were conducted to indicate if there were differences between exophagic and endophagic behavior. The seasonality of Mansonia species was also analyzed. Overall, 96,766 specimens were collected over five years of sampling. Mansonia titillans (Walker) was found to be the most abundant species (76.9%). The highest percentage of mosquitoes was collected in February (48.4%), followed by October (39.6%) and June (12.0%). The biting activity of the two most abundant species showed peak host seeking activity/behavior during twilight and night, more perceptible in the outdoor environment (peridomiciliary). In general, seasonality showed a tendency towards a reduction in the abundance of Mansonia in the years after 2015. Our results will be essential in the formulation of effective control methodology for Mansonia in the studied area.
Keywords: exophilic; mosquitoes; visiting behavior